Impact of dislocations and dislocation substructures on molten salt corrosion of alloys under plasticity-imparting conditions. (November 2020) - Muránsky, Ondrej; Karatchevtseva, Inna; Danon, Alexander E.; Holmes, Rohan; Huai, Ping; Zhang, Zhaoming
Graphical abstract: Highlights: The state of the alloy's microstructure and its in-service evolution affects its corrosion behaviour. High-temperature creep leads to the storage of dislocation and development of dislocation substructure. Dislocation substructure promotes intragranular diffusion of alloying elements to the salt-alloy interface. Accelerated diffusion of alloying elements leads to an increased corrosion attack of the alloy. Abstract: Molten-salt-based energy-generation and energy-storage systems are expected to function under plasticity-imparting in-service operating conditions. It is thus of utmost importance to understand the effect of these operating conditions on the corrosion performance of molten-salt-facing structural alloys. Here, we investigate the impact of high-temperature creep on the molten salt corrosion of a NiMoCr alloy in FLiNaK molten salt. We show that high-temperature creep leads to an increased susceptibility of the alloy to molten salt corrosion via the development of a dislocation substructure, which promotes mass diffusion of alloying elements towards the salt–alloy interface (exposed surface). In addition, the corrosion-affected near-surface layer undergoes recrystallization leading to a significant increase in the amount of grain boundaries, which further promotes ongoing diffusion processes. This then causes increased molten salt corrosion attack resulting in an accelerated mass loss during the alloy's exposure to the molten salt. The present results thus unambiguously highlight the importance of the state of the microstructure as well as the evolution of the microstructure under in-service operating conditions on the alloy's molten salt corrosion performance.